2020
DOI: 10.1186/s12888-019-2417-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving the psychometric properties of the dissociative experiences scale (DES-II): a Rasch validation study

Abstract: Background: The Dissociative Experiences Scale-II (DES-II) is a self-report questionnaire that measures dissociative experiences such as derealization, depersonalization, absorption and amnesia. The DES-II has been prevalently used as a screening tool in patients suffering from psychotic disorders or schizophrenia. However, dissociative experiences can also be part of normal psychological life. Despite its popularity, the most problematic aspect of the DES-II is the inconsistency in its factor structure, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…These findings demonstrated that the psychometric characteristics of the Indonesian LOT-R are an important addition for the Indonesian researchers. In line with a previous research, and from a practical perspective, the findings from the Rasch analysis may allow psychologists and non-specialists to confidently interpret sum scores as good indicators of individuals' optimism (e.g., Saggino et al, 2020). This is also in line with the original scoring method proposed by the LOT-R developers (see Scheier et al, 1994).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These findings demonstrated that the psychometric characteristics of the Indonesian LOT-R are an important addition for the Indonesian researchers. In line with a previous research, and from a practical perspective, the findings from the Rasch analysis may allow psychologists and non-specialists to confidently interpret sum scores as good indicators of individuals' optimism (e.g., Saggino et al, 2020). This is also in line with the original scoring method proposed by the LOT-R developers (see Scheier et al, 1994).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, while LOT-R is theoretically unidimensional and has a bipolar construct (e.g., Chiesi et al, 2013;Steca et al, 2015) that fulfils the unidimensionality requirement of the Rasch measurement (Wright & Masters, 1982), the debate over its dimensionality remains unsolved (Schou-Bredal et al, 2017). Unidimensional measures, as per the Rasch model, are more appropriate for statistical analyses because the differences between participants' scores are interval-scaled, and the total score is an adequate representation of the construct measured by the scale used (Saggino et al, 2020). Therefore, in this study, we hypothesized a unidimensional model of the Indonesian LOT-R.…”
Section: The Rasch Measurement Modelmentioning
confidence: 99%
See 3 more Smart Citations